2017
DOI: 10.17265/1537-1514/2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Reward on Job Satisfaction and Performance: Implications for Blue Collar Employees

Abstract: Job satisfaction has been tested and proven as one of the factors that connect employees to their organization.Additionally, job satisfaction leads to better employee performance. Hence, the main purpose of this study is to investigate the impact of financial rewards on job satisfaction and employee performance of the Blue Collar employees in the construction, contracting and printing industries in Lebanon. The data for this study were collected using self-administered questionnaires from 250 employees working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of this study are also supported by the research of (Zaraket & Saber, 2017) and (Addai, Kyeremeh, Abdulai, & Sarfo, 2018) who suggested that higher rewards for employees at work play an important role both in the advancement of employee job satisfaction and higher profitability in associations. Higher rewards for employees in the workplace play an important role in both advancing employee job satisfaction and higher profitability in the association.…”
Section: Rewards Affects Directly Positive On Job Satisfactionsupporting
confidence: 84%
“…The results of this study are also supported by the research of (Zaraket & Saber, 2017) and (Addai, Kyeremeh, Abdulai, & Sarfo, 2018) who suggested that higher rewards for employees at work play an important role both in the advancement of employee job satisfaction and higher profitability in associations. Higher rewards for employees in the workplace play an important role in both advancing employee job satisfaction and higher profitability in the association.…”
Section: Rewards Affects Directly Positive On Job Satisfactionsupporting
confidence: 84%
“…This study is in accordance with the theory of motivation which states that an individual is motivated to perform a task to fulfill needs, such as psychological needs, safety and security needs, as well as social needs. Once these requirements are met, financial rewards are then considered (Zaraket & Saber, 2017). This study is in accordance with the results of research conducted by (Jumiati, 2018b) that analyzed Professional Training on Career Selection with Financial Rewards as a Moderating Variable.…”
Section: Professional Training On Career Selection With Financial Rew...mentioning
confidence: 99%
“…Employee performance is influenced by remuneration structure, Wael and Farouk (2017) demarcated remuneration as pay or reward given to persons for a job done. He further identified the indicators of remuneration include; basic salary, wages, health schemes, pension schemes, transport allowances overtime allowances, and responsibility allowances.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Wael and Farouk (2017) financial rewards contain pay, bonuses, transportation facility, health insurance, and pensions. As a result, employees receive financial payments from their employers in the form of salaries or commissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation